Impact of COVID-19 on food safety and security in low and middle income countries - Uddin, Md Nasir; Alam, Badrul; Islam, SK Shaheenur; Arif, Mohammad; Alam, Md Mahbubul; Kabir, S M Lutful (Asian Journal of Medical and Biological Research, 2020)
The occurrence of COVID-19 which causes severe acute respiratory infection has produced a large global outbreak with major public health concern. Since Chinese wet market (LBM) has been blamed to be linked with this global pandemic of COVID-19 as the noble virus has supposed to be transmitted from a wild species, however, this is not yet established the association of SARS-Cov-2 transmission via animal to human or food chain. Moreover, it has been recognized to spread human-to-human transmission by inhalation of droplets or direct contact. Besides the devastating effects of SARS-Cov-2, world has been experiencing the impact of food safety and security as the effect due to global lockdown resulting a wide range of new challenges of economic growth and societal burden. In this review, we have focused on effect of corona virus on food system that included food safety, food security during lockdown, and prevention and control options have been emphasized to keep normalcy of livelihood of general people in low and middle income countries (LMICs). Since the global economy has been downed deeper into a financial crunch, the government efforts are underway to bolster up the priorities with the limited resources, and further funding allocation decision is obligatory for the targeted communities those are affected most due to the swath of pandemic threat of COVID-19. Asian J. Med. Biol. Res. June 2020, 6(2): 130-137